2008
DOI: 10.1042/bj20081073
|View full text |Cite
|
Sign up to set email alerts
|

Atp6v1c1 is an essential component of the osteoclast proton pump and in F-actin ring formation in osteoclasts

Abstract: Synopsis Bone resorption relies on the extracellular acidification function of vacuolar ATPase (V-ATPase) proton pump(s) present in the plasma membrane of osteoclasts. The exact configuration of the osteoclast-specific ruffled border V-ATPases remains largely unknown. In this study, we found that the V-ATPase subunit Atp6v1c1 (C1) is highly expressed in osteoclasts while subunits Atp6v1c2a (C2a) and Atp6v1c2b (C2b) are not. The expression level of C1 is highly induced by RANKL during osteoclast differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 41 publications
7
130
0
Order By: Relevance
“…We performed immunofluorescence analysis as we described previously (18), with the exceptions that we used rat polyclonal anti-CD3 (Abcam, Cambridge, MA) as the primary antibodies and observations were performed by epifluorescence in a Zeiss Axioplan microscope (Carl Zeiss Microscopy, LLC, USA). Nuclei were visualized with 1 g/ml DAPI (4=,6-diamidino-2-phenylindole) (SigmaAldrich, USA).…”
Section: Animalsmentioning
confidence: 99%
“…We performed immunofluorescence analysis as we described previously (18), with the exceptions that we used rat polyclonal anti-CD3 (Abcam, Cambridge, MA) as the primary antibodies and observations were performed by epifluorescence in a Zeiss Axioplan microscope (Carl Zeiss Microscopy, LLC, USA). Nuclei were visualized with 1 g/ml DAPI (4=,6-diamidino-2-phenylindole) (SigmaAldrich, USA).…”
Section: Animalsmentioning
confidence: 99%
“…24 ATP6V1C1, a c subunit of the V-ATPase, also appears to be important for lysosome acidification in osteoclasts and co-localizes with the a3 subunit at the ruffled border in vitro. 25 Finally, cell culture experiments have demonstrated that ATP6AP1 (AC45), an accessory subunit of the V-ATPase, 26 is required for extracellular acidification in osteoclasts, possibly by playing a role in the proper localization of the V-ATPase complex. 27 Since there is a massive transport of protons toward the lacuna during bone resorption, it was assumed that a parallel transport of anions (Cl − ) must take place simultaneously in order to maintain electroneutrality within the osteoclast.…”
Section: Lysosomal Proteins Implicated In the Lacuna Acidificationmentioning
confidence: 99%
“…These genes interact to maintain normal metabolic activity. These include transmembrane protein 50A (TMEM50A) located in RH gene locus, ATP6V1C1 which regulates extracellular acidification to facilitate bone resorption (Feng et al, 2009) and PRKAR1A inhibits protein phosphorylation and tumour development (Bossis and Stratakis, 2004;Groussin et al, 2002). Mutations in PRKAR1A have been associated with tumour development (Scott, 1991;Tasken et al, 1997).…”
Section: Other Cellular Processesmentioning
confidence: 99%